PERAN STRATEGIS GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR PADA SISWA DIGITAL NATIVE - Anggraini, Khusnul Widya; Liestyasari, Siany Indria (FISIP Universitas Malikussaleh, 2025)
This study aims to analyze the learning strategy of sociology teachers at Al Islam 1 High School in Surakarta. The approach used in this research is a qualitative approach with the type of case study. Researchers collected in-depth descriptive data through observations, interviews, semi-structured questionnaires, and documents related to learning at school. The informants of this study consisted of two sociology teachers and students of class X 9, X 2, XI 7, and XI 10 who were selected using purposive sampling technique. Data sources through classroom observations, teacher and student interviews, and semi-structured questionnaires to obtain perspectives on the application of effective learning strategies. Data validity was tested using source triangulation and technique triangulation to ensure accuracy and consistency of information. Primary data was obtained from observations, interviews, and teaching modules. Secondary data was obtained from articles, journals and documentation. This research can provide insight into the internal and external factors that influence the success of learning strategies by teachers, especially in facing the challenges of digital technology among digital native students. Ausubel's learning theory is used as a foundation to design learning strategies that connect new knowledge with existing knowledge, thus creating meaningful learning experiences contextually. Meaningful learning associated with sociology material is very relevant to creating contextual based learning.